Estudo fitoquímico e quimiossitemático de Galipea, Swinglea (Rutaceae) e avaliação do potencial biológico dos compostos isolados - Cerqueira, Cristovam do Nascimento (2011)
The Galipea genus species classifications has been confuse since genus classification. Showing no agreement among taxonomists in several classification systems since 1823. However, Kallunki & Pirani corrected errors exist in the ancient botanical classification reclassify several species of Galipeas like Conchocarpus or Angostura. Thus, it was chosen a specie of Galipea (G. carinata) and one Angostura (A.bracteata) which previously belonged to Galipea in order to evaluate a possible parallelism between the classification proposed by Kallunki & Pirani with the chemical profile of the species studied. The phytochemical studies of the A. bracteata and G. carinata no led to the isolation of the secondary metabolites, though the research literature shows a relation of parallelism between the botanical classification based on morphology of species of the genus with the same chemical this one, but this relationship was only apparent when you compare the already isolated Conchocarpus s alkaloids with those of Angostura, where it was discovered that the alkyl and alquilarilquinolinicos alkaloids present in Angostura, are absent in Conchocarpus. In turn, the acridones and indolquinazolínicos alkaloids found in Conchocarpus were not observed in Angostura. The comparison of the aforementioned genres with Galipea was not discussed due to the few reported alkaloid (2-quinolone) for the species of this genus can not be classified as this specific. The Swinglea glutinosa, a species native to Asia, possesses many reports acridones alkaloids and coumarins isolated from its fruit, stem and roots, but these metabolites are reported from polar extracts, thus having no knowledge whatsoever of metabolites of low polarity. This work is also aimed at expanding the knowledge of the chemical profile of this species. The phytochemical study of S. glutinosa led to the isolation of two triterpenes: 3α-Hidroxiglutin-5-ene (08) and friedelin (09), a diterpene (2Z)-2-methyl-[2,5,5,8 a-tetrametildecaidronaftalen-1-yl] but-2-en-1-ol (07), two steroids, sitosterol (10) and stigmasterol (11), a flavanone: pinostrobine (07) and three amides: N-benzoiltiramida (01), N-{2 - [4 - (3-oxobutoxyl) phenyl] ethyl} benzamide (02), 2 (E) N-methyl-fenilacrilamide (05), the latter being new in the literature. The amide N-{2 - [4 - (2,3-dihydroxy-3-methyl-4-oxobutoxyl) phenyl] ethyl} benzamide (03) and carboxylic acid (04) acid 4 - {4 - [2 - (benzoilamino ) ethyl] phenoxyl} -2.3-dihydroxy-2-methylbutanoic was identified by GC-MS, where these two metabolites enhance the biogenesis of novel amide via O-prenylation then the loss due to carbon dioxide in several oxidations methyl terminal. Some of the compounds have their biological activity by testing tested against the Guignardia citricarpa of growth either in vitro mycelial where only the substance (08) showed an inhibition of about 50% and substance (07) stimulated the growth of the fungus. In the inhibition test of germination and appressorium formation, which evaluates the inhibition of fungal reproductive structure that is the main way of infection, the substance (08) showed an inhibition of 93.5% and 96.5% germination and training appressoria, respectively. The substance (02) inhibited 90.5% and 94.5% germination in appressorium formation. Thus, this work took place some fungicidal compounds with potential to control the fungus G. citricarpa.